Production management model through MPS and line balancing to reduce the non-fulfillment of orders in lingerie clothing MSEs in Peru - Flores-Andrade, K. (2020)
The focus of this research is to establish control and planning management in the sewing production process of lingerie clothing to better prepare companies for demand growth. The lack of improvement tools in this sector, the lack of staff training and a lack of quality culture has led to companies, especially MYPES, not being able to meet the established delivery times and non-fulfillment of orders with the customers, which represents 80% of dissatisfied orders due to the limited production capacity and non-productive time in the plant. This problem is due to limited production capacity, deficient production planning, and lack of materials. In order to solve this problem, industrial engineering tools were used. The application of these tools improved production from 79% to 95%.